PENGARUH KETIDAKSEIMBANGAN BEBAN TERHADAP PROFIL JARINGAN TEGANGAN RENDAH - Krisna Yoga, I Kadek; Sari Hartati, Rukmi; Ariastina, Wayan Gede (Jurnal SPEKTRUM; Vol 10 No 2 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i02.p1, 2023)
Load imbalance occurs due to unequal distribution of load in each phase, this can occur in low voltage network distribution lines, one of which occurs in the DS0588 transformer, Merdeka feeder, Denpasar. Based on the data obtained, the percentage of DS0588 transformer load unbalance is 14%. The DS0588 transformer is one of the transformers at the Merdeka Denpasar Feeder with a capacity of 160 kVA which is located on Jalan Badak Agung, Renon Denpasar. Load unbalance data obtained at PLN UP3 South Bali. The research was carried out by the method of redistribution of the load on each phase under unbalanced load conditions, so that the total load of the three phases is the same or close. The results obtained were that the percentage of unbalanced loads in unbalanced conditions was 14% and when balanced conditions decreased to 2.2%. The losses in the distribution network when the unbalanced condition is 25 kW and the balanced condition drops to 23.3 kW, this shows that the load imbalance has an effect on the low voltage network losses. The higher the load imbalance, the higher the losses incurred.